Innovation of a Technological Product with Utilizing the Target Costing Methodology - PotkÃ¡ny, Marek; NovÃ¡k, Petr; KovÃ¡Ä, RÃ³bert; Hitka, MiloÅ¡ (International Review of Management and Marketing, 2017)
The modern business environment is characterized by high competitiveness. If an enterprise wishes to maintain a competitive edge and hang on to clients, it is very important to engage in innovative activities, even if there is no real justification for doing so. Such innovation in the business environment and cost structure is additionally a catalyst for change in cost management. Gradually, costs begin to be seen from a strategic perspective and planning is undertaken in the preproduction phase, as a consequence of this stage creating the greatest impact on any future success of a product. Varying perceptions of costs and the behavior pertaining to them also necessitates that adequate tools are developed for their strategic management, e.g. target costing. The aim of this paper is to present the upgrade of an electronic item - a sports LED display, adapting it to be compatible with external devices running the Android operating system, in accordance with cost projection applied via the target costing methodology. Doing a target costing calculation through the procedure proposed allows for functional differentiation of the given product, specifically to satisfy the requirements of potential customers at an acceptable market price. Keywords: Cost Projection, Calculation, Target Costing, Innovation JEL Classifications: M21, M41, O31